Single Step Joint: overview of European standardized approaches and experimentations - Verbist, Maxime (2017)
In the field of Built Heritage Restoration, engineers have to work with old structures made of poorly preserved timber elements. The assessment of timber elements and connections is a major issue for engineers involved in a restoration project. Before thinking about any intervention techniques, engineers have to properly understand how the carpentry connections fail, which parameters influence the failure modes (e.g. geometry of the joint, mechanical properties of the wood) and how the internal forces are distributed into the joint to finally figure out how to design the traditional carpentry connections. The present paper aims at raising those questions focusing on the Single Step Joint (SSJ) design. Even if this common joint between the rafter and the tie beam is geometrically simple, one may pick up three SSJ families from the past till today: the Geometrical Configuration Ideal Design, the Geometrical Configuration Perpendicular to the Tie Beam and the Geometrical Configuration Perpendicular to the Rafter. The first one is more recent because its geometry requires accurate timber cutting, using new technologies (e.g. Computer Numerical Control). For each one, some general design rules about the SSJ geometrical parameters are defined by some European standards (e.g. Eurocode 5 in Design of timber structures-part 1-1: general-common rules and rules for buildings. CEN, European Standardisation Institute, Brussels, 8) or authors (e.g. Siem and Jorissen in Shatis' 15: 3rd international conference on structural health assessment of timber structure, vol 1. Wroclaw, Poland, 9-11 Sept 2015, 11), but no detail is available on how to design this connection in order to prevent the shear crack at the heel depth in the tie beam, or the compressive crushing at the front-notch surface. Hence the design rules and the emergence of failure modes must be defined according to the SSJ geometrical parameters. In order to check the design equations and the failure modes, lab tests on the three SSJ families have been carried out, mo